Control Design on a Non-minimum Phase Nonlinear System by Output Redefinition and Particle Swarm Optimization Method - Ahmadin Ahmadin; Fatmawati Fatmawati; Edi Winarko; Windarto Windarto (Statistics, Optimization & Information Computing, 2025)
In this paper, we study the control design of a non-minimum phase nonlinear system. Here we investigate a nonlinear system in a particular class and use coordinate transformation to determine the normal form of the system. We present some theorems that state a non-minimum phase nonlinear system becomes the minimum phase with a new output. We further use the new output to determine the control variable, and we use particle swarm optimization to determine the desired output of the output that has been selected. From this design, the output of the system can track the desired output of the original system.